"May the Force move you": Roles and actors of information sharing devices in urban mobility. (May 2019) - Vecchio, Giovanni; Tricarico, Luca
Abstract: The innovation recently brought into the market for mobility innovation (by apps, social networks and sharing economy practices) impacts upon the economic appeal of urban areas and strongly influences the preferences of individuals in happiness, lifestyles and related aspect of urban consumption. Several sharing devices are nowadays producing such effects, offering innovative solutions to support the availability of mobility supply. They do so by conveying useful tools to the whole community of users, by proposing new ways of producing knowledge and services, and by favoring symmetric information in the urban mobility market. The paper aims to discuss the impact of these innovation devices in shaping individual's mobility preferences, by drawing on a wide set of experiences that have introduced new technologies and shared mobility practices that provide significant information related to mobility. Drawing on a literature review referred to a wide set of new technologies and shared mobility practices based on significant information related to mobility, the paper draws its discussion on three analytical dimensions: the role that information has in shaping individual mobility choices, and how it may interact with individual preferences and needs; the varied forms of relevant mobility information made available by information-sharing devices; the many actors (corporations, public administrations, community groups…) who produce information collecting data and making them available in different forms. Drawing on these elements, a policy framework is discussed, to define suitable operational approaches to urban mobility that are more attentive to individual needs and more effective in terms of sustainability. Highlights: Information-sharing devices contribute to shape individuals' mobility choices. Devices make available both objective and subjective forms of information. Emerging actors like corporations and communities produce and make information usable. Information allows unprecedented initiatives addressing individual mobility behaviours. A policy framework for information-based initiatives is provided.